VIDEO-BASED FAMILY NURSING: PREPARING SCHOOL-AGED CHILDREN FOR THE COVID-19 NEW NORMAL - Andra Saferi Wijaya; Septiyanti Septiyanti; Apreni Saputri; Padila Padila (Proceeding B-ICON, 2023)
Families are the smallest group in society that can contribute to preventing COVID-19 transmission in the new normal. Especially the role of parents in providing education in the family, especially for schoolchildren, to prevent the transmission of COVID-19. The purpose of this study is to determine the effect of video-based family nursing therapy on family independence in preparing schoolchildren to face the new normal of COVID-19 in Bengkulu City in 2021. The design of this study is quasi-experimental with pre- and post-tests with a control group. The research was conducted in Kuala Lempuing Village, Bengkulu City, in September–December 2021. The total sample size of the study was 30 respondents for the intervention and 30 respondents for the control group. Data processing is carried out using the Paired Sample T Test because the data is normally distributed. The analysis results show a value of p = 0.000. Based on the results of the study, it can be concluded that there are significant differences in family independence in the treatment group after a video-based family nursing intervention. The results of this study recommend that community nurses can take a family nursing care approach to providing education to the community and be independent in preparing children for face-to-face learning.